The epidemiology and management of clusters of invasive meningococcal disease in England, 2010–15. (3rd April 2019) - Gobin, Maya; Hughes, Gareth; Foulkes, Sarah; Bagnall, Helen; Trindall, Amy; Decraene, Valérie; Edeghere, Obaghe; Balasegaram, Sooria; Cummins, Amelia; Coole, Louise
Abstract: Background: Guidance for public health management of invasive meningococcal disease (IMD) in in England recommends the use of antibiotic chemoprophylaxis and vaccination. We summarized clinical and epidemiological data collected during routine management of IMD clusters in England. Methods: Data on epidemiology and operational decisions for public health management were reviewed for clusters between April 2010 and December 2015. Results: Clusters were generally 2–3 cases (53/58; 91%) within a single age band <18-years. Nurseries ( n = 20, 34%), households/social networks ( n = 14, 24%) and schools ( n = 10, 17%) were the commonest settings. Chemoprophylaxis alone was used in 36 (58%) clusters, including most serogroup B clusters (31/41; 76%). Chemoprophylaxis and vaccination was used in a further 20 (32%) clusters. Vaccine was delivered promptly (<7 days). Four clusters had cases with onset post-chemoprophylaxis; no clusters recorded cases with onset post-vaccination. No pattern was observed between interventions and setting/population at risk, and interventions were consistent with national guidance. Challenges to management included logistical issues related to intervention delivery. Conclusions: Public health management of IMD clusters presents challenges in decision-making and implementation of interventions. Nonetheless, few cases were observed following intervention. Responses were consistent with national guidance. A systematic data collection tool should be developed to support future evaluation.